2014
DOI: 10.1016/j.bbi.2013.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Six weeks of voluntary wheel running modulates inflammatory protein (MCP-1, IL-6, and IL-10) and DAMP (Hsp72) responses to acute stress in white adipose tissue of lean rats

Abstract: To prime local tissues for dealing with potential infection or injury, exposure to an acute, intense stressor evokes increases in circulating and local tissue inflammatory proteins. Regular physical activity facilitates stress-evoked innate reactivity and modulates the expression of inflammatory proteins in immuno-metabolic tissues such as white adipose tissue (WAT). The impact of regular physical activity on stress-evoked inflammatory protein expression in WAT, however, remains unclear. To investigate this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…In support of our data, others have shown that 6 weeks of VWR 38 and exercise training 30 protect against acute stressors. For example, our group has shown that exercise training offers protection against adipose tissue inflammation induced by the b-3 adrenergic agonist CL 316, 243.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In support of our data, others have shown that 6 weeks of VWR 38 and exercise training 30 protect against acute stressors. For example, our group has shown that exercise training offers protection against adipose tissue inflammation induced by the b-3 adrenergic agonist CL 316, 243.…”
Section: Discussionsupporting
confidence: 80%
“…30 In this study, protective effects were primarily observed in eWAT for indices of IL-6 signaling as marked by the mRNA expression of IL-6 and SOCS3, along with the mRNA expression of TNF-a, yet a similar effect did not occur in iWAT. Others 38 have demonstrated that 6 weeks of VWR alters the response to acute tail shock stress in rats. They found that VWR led to an increase in the protein content of MCP-1, IL-6, and IL-10, and a decrease in the ratio of pro-inflammatory to anti-inflammatory proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When the immune system is challenged, an important flow of energy is required. The metabolic potential of adipose tissue and the energy needs of the immune system have probably led to the evolutionary development of feedback relationships between the two systems (Batra and Siegmund 2012;Lago et al 2007;Speaker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, diabetic or metabolic syndrome males put on a 3-week daily exercise program showed significant reductions in body mass index, serum lipids and cholesterol, fasting glucose, insulin, macrophage inflammatory protein-1alpha, matrix metalloproteinase-9 and C-reactive protein (CRP) [64,65]. Moreover, voluntary habitual exercise augments the innate immune system, through increases in stressevoked heat shock protein 72 (Hsp72), MCP-1, IL-6 and IL-10 and decreases inflammatory cytokines IL-1 beta and TNF-alpha [66]. In addition, soluble intercellular adhesion molecule-1 (sICAM-1) levels are significantly improved in physically active type-2 diabetic patients [67].…”
Section: Keeping the Metabolic Balance Through Exercisementioning
confidence: 99%